2011
DOI: 10.1002/cncr.25940
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal cancer and brain metastasis

Abstract: Metastatic brain tumors represent 20% to 40% of all intracranial neoplasms and are found most frequently in association with lung cancer (50%) and breast cancer (12%). Although brain metastases occur in <4% of all tumors of the gastrointestinal (GI) tract, the incidence of GI brain metastasis is rising in part due to more effective systemic treatments and prolonged survival of patients with GI cancer. Data were collected from 25 studies (11 colorectal, 7 esophageal, 2 gastric, 1 pancreatic, 1 intestinal, 3 all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
82
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(94 citation statements)
references
References 50 publications
(124 reference statements)
2
82
1
Order By: Relevance
“…On the contrary, pancreatic cancer metastases to the brain are exceedingly rare (0.33 % of pancreatic adenocarcinoma cases as per Pauline et al [4] vs. 0.57 % as per Park et al [5]), perhaps owing to the aggressive nature of pancreatic adenocarcinoma and the fact that most patients do not survive long enough to experience clinical manifestations of brain metastasis. It is also a possibility that the actual incidence is higher than reported as many patients may not be evaluated for a CNS lesion as first presentation late in the course of the disease is extremely common with pancreatic carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, pancreatic cancer metastases to the brain are exceedingly rare (0.33 % of pancreatic adenocarcinoma cases as per Pauline et al [4] vs. 0.57 % as per Park et al [5]), perhaps owing to the aggressive nature of pancreatic adenocarcinoma and the fact that most patients do not survive long enough to experience clinical manifestations of brain metastasis. It is also a possibility that the actual incidence is higher than reported as many patients may not be evaluated for a CNS lesion as first presentation late in the course of the disease is extremely common with pancreatic carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…BMs from CRC are far less frequent and have been reported to occur in approximately 1-4% of patients [5][6][7]. Due to cancer patients surviving longer and the advance in imaging techniques aiding increased detection, the incidence of colorectal BM is increasing.…”
Section: Introductionmentioning
confidence: 98%
“…However, the overall incidence of brain metastases in gastrointestinal cancers patients is relatively low [8,9,10]. Other reports that have pooled information either from several other clinical studies and autopsy studies [11] or only from autopsy series [12] have suggested that the frequency of brain metastases varies from 1 to 5% in all EC patients. Interestingly, a recent report [8] suggested that the frequency of brain metastases was higher in EAC patients (12.1%) compared to patients with squamous cell carcinoma (1.4%) histology.…”
Section: Introductionmentioning
confidence: 99%